Bimbingan Kekayaan Intelektual Merek Jasa “Kelas 35” Paguyuban Batik Tulis Kebon Indah, Bayat, Klaten - Muafi Muafi; Rizqi Adhyka Kusumawati (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
The Kebon Indah Batik Tulis Society currently has a registered brand with the Ministry of Law and Human Rights since 2010 with the brand name "Kebon Indah". Outside the Paguyuban, there are similar trademark registrations by other parties, so it is necessary to register for an extension of the “Kebon Indah” trademark protection period. The specific purpose of this service activity is to provide technical guidance on the registration of the extension of the "Kebon Indah" brand protection period and register the "Kebon Indah" brand in the service business category. The method of service activities will use an intense mentoring method, namely assistance with field practice techniques so that partners are the main actors in this activity. The mentoring method consists of 5 core stages, namely 1) Discussion, 2) Preparation of service mark registration files, 3) Technical guidance on trademark or service mark registration, 4) Registering with the Ministry of Law and Human Rights and 5) Ongoing mentoring. The service activities have been carried out well and the results are very satisfying. In the context of sustainable activities going forward, various activities will be carried out such as socializing about Marketing, Digital Marketing, utilization of social media, work motivation, enrichment of natural dyes and others.